THU0175 Inflammation detected with modern sensitive mri analysis demonstrates that therapeutic response as early as one month predicts 12-month radiographic progression: data from a study using tofacitinib and methotrexate in methotrexate-naÏve patients with early ra. (15th June 2017) - Conaghan, PG; Bowes, MA; Østergaard, M; Guillard, G; Chapman, D; Stein, A; Andrews, J; Xie, Z; Koenig, A; Soma, K; Wilkinson, B
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of RA. A novel automated quantification method for RA MRI-detected pathology using statistical shape modelling technology (RAMRIQ) provides a tool that may be even more responsive than the sensitive RAMRIS semi-quantitative standard. 1 Objectives: To determine if early changes in RAMRIQ were predictive of subsequent MRI and radiographic damage progression in a study of tofacitinib for the treatment of early RA in methotrexate-naïve patients with minimal radiographic progression. Methods: We used data from an exploratory, Phase 2 randomised controlled trial comparing tofacitinib, methotrexate and the combination (n=109) in methotrexate-naïve patients with early active RA. 1 All patients met ACR classification criteria for active RA. MRI was performed at baseline and at 1, 3, 6 and 12 months. A single centralised reader read all MRI data; data for each patient were randomised by time point and read in the same sitting. We examined changes in synovitis, osteitis and erosions for RAMRIQ and RAMRIS at 1 and 3 months and performed univariate analyses on their relationship to RAMRIS, RAMRIQ and radiographic progression (modified Total Sharp Score [mTSS]) at 12 months. Results: Reduction in RAMRIQ synovitis and osteitis at 1 and 3 months were significantly associated with reduction in RAMRIS erosion progression at 12 months (Table). Improvement in RAMRIQ synovitis and osteitis at 1 and 3 months were also associated with reduction in radiographic progression at 12 months, while RAMRIQ erosions at 1 and 3 months were not significantly associated with radiographic progression (Table). Early changes in RAMRIS erosion at 1 and 3 months were associated with radiographic progression at 12 months (Table). Treatment with tofacitinib alone or in combination with methotrexate was also associated with reduced progression in RAMRIS erosions (p=0.017 and p=0.007, respectively). Conclusions: In this study, sensitive automated detection demonstrated that change in synovitis and osteitis predict subsequent RAMRIS erosion and radiographic progression. Treatment with tofacitinib as monotherapy or in combination with methotrexate was also highly predictive of no progression of erosive damage. Because of its enhanced sensitivity, novel quantitative imaging analysis has the potential to change RA clinical trial design where assessing structural damage is an objective. References: Conaghan PG et al. Ann Rheum Dis 2016; 75: 1024–1033. Acknowledgements: Previously presented at ACR 2016 and reproduced with permission. This study was sponsored by Pfizer Inc. Editorial support was provided by S Morgan of CMC and was funded by Pfizer Inc. Disclosure of Interest: P. G. Conaghan Consultant for: AbbVie, Eli Lilly, Flexion, Novartis, Pfizer Inc, Roche, Speakers bureau: AbbVie, Novartis, Roche, M. A. Bowes Employee of: Imorphics Ltd, M. Østergaard Grant/research support from: AbbVie, Centocor, Merck, Consultant for: AbbVie, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Eli Lilly, GSK; Hospira, Janssen, Merck, Mundipharma, Novartis, Novo, Orion, Pfizer Inc, Regeneron, Roche, Schering-Plough, Takeda, UCB, Wyeth, Speakers bureau: AbbVie, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Eli Lilly, GSK; Hospira, Janssen, Merck, Mundipharma, Novartis, Novo, Orion, Pfizer Inc, Regeneron, Roche, Schering-Plough, Takeda, UCB, Wyeth, G. Guillard Employee of: Stryker Co, D. Chapman Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Stein Employee of: Quintiles, J. Andrews Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Z. Xie Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Koenig Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Soma Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Wilkinson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc